Quan xin quan yi.
Coloured Chinese propaganda poster promoting Lei Feng's spirit of selfless. It depicts a young woman carrying a large bag of food on her shoulder while assisting an elderly woman at the same time. A little boy carrying a red lantern leads the way. A few small sized books in the boy's pocket, the front one titled "The Story of Lei Feng".
Chinese Propaganda Posters - With All Your Heart and All your Mind.
Also available online
Keywords: China -- History -- Cultural Revolution, 1966-1976 -- Posters